Kinetic model of carbonate dissolution in Martian meteorite ALH84001 - Kopp, Robert E.; Humayun, Munir (Geochimica et Cosmochimica Acta, 2003)
The magnetites and sulfides located in the rims of carbonate globules in the Martian meteorite ALH84001 have been claimed as evidence of past life on Mars. Here, we consider the possibility that the rims were formed by dissolution and reprecipitation of the primary carbonate by the action of water. To estimate the rate of these solution-precipitation reactions, a kinetic model of magnesite-siderite carbonate dissolution was applied and used to examine the physicochemical conditions under which these rims might have formed. The results indicate that the formation of the rims could have taken place in < 50 yr of exposure to small amounts of aqueous fluids at ambient temperatures. Plausible conditions pertaining to reactions under a hypothetical ancient Martian atmosphere (1 bar CO2), the modern Martian atmosphere (8 mbar CO2), and the present terrestrial atmosphere (0.35 mbar CO2) were explored to constrain the site of the process. The results indicated that such reactions likely occurred under the latter two conditions. The possibility of Antarctic weathering must be entertained, which, if correct, would imply that the plausibly biogenic minerals (single-domain magnetite of characteristic morphology and sulfide) reported from the rims may be the products of terrestrial microbial activity. This model is discussed in terms of the available isotope data and found to be compatible with the formation of ALH84001 rims. Particularly, anticorrelated variations of radiocarbon with δ13C indicate that carbonate in ALH84001 was affected by solution-precipitation reactions immediately after its initial fall (ca. 13,000 yr ago) and then again during its recent exposure prior to collection.